2003
DOI: 10.1038/sj.onc.1206038
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regression by combination antisense therapy against Plk1 and Bcl-2

Abstract: Increased expression of the cell proliferation-associated polo-like kinase 1 (PLK1) and apoptosis-associated BCL-2 genes has been observed in different human malignancies. Inhibition of cell proliferation and reactivation of apoptosis are basic principles in anticancer therapy. The efficiency of this approach is often limited by insuf-ficient targeting and delivery of anticancer drugs into the tumors. Phosphorothioate antisense oligodeoxynucleotides (ODNs) directed against PLK1 and BCL-2 were administered syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 40 publications
(45 reference statements)
2
55
1
Order By: Relevance
“…This has been shown for the two subtypes of mitotic catastrophe mentioned above (Minn et al, 1996;Ferri et al, 2000a;Castedo et al, 2001Castedo et al, , 2004aRoumier et al, 2003;Perfettini et al, 2004), again underlining the importance of the apoptotic machinery (and in particular of the intrinsic, mitochondrial pathway) for the execution of mitotic catastrophe. In accord with this notion, it has also been shown that inhibition of Bcl-2 expression by antisense oligonucleotides can actually facilitate and amplify mitotic catastrophe (Elez et al, 2003).…”
Section: Mitotic Catastrophe and The Apoptotic Machinerymentioning
confidence: 57%
See 1 more Smart Citation
“…This has been shown for the two subtypes of mitotic catastrophe mentioned above (Minn et al, 1996;Ferri et al, 2000a;Castedo et al, 2001Castedo et al, , 2004aRoumier et al, 2003;Perfettini et al, 2004), again underlining the importance of the apoptotic machinery (and in particular of the intrinsic, mitochondrial pathway) for the execution of mitotic catastrophe. In accord with this notion, it has also been shown that inhibition of Bcl-2 expression by antisense oligonucleotides can actually facilitate and amplify mitotic catastrophe (Elez et al, 2003).…”
Section: Mitotic Catastrophe and The Apoptotic Machinerymentioning
confidence: 57%
“…The overexpression of a DN Plk1 has also been reported to induce a G2/M arrest, mitotic alterations (but with frequent monoastral mitoses) and apoptosis (Cogswell et al, 2000). An antisense approach designed to reduce the expression of Plk1 has therapeutic effects on human tumors xenotransplanted into immunodeficient mice, in particular, when combined with antisense Bcl-2 (Elez et al, 2003), suggesting that it does involve apoptosis.…”
Section: Plks In Mitotic Catastrophementioning
confidence: 99%
“…While early works in this field concentrated mainly on the identification of Polo homologues in different species and on the role of this enzyme family in normal tissue development and mitosis, the focus of interest has changed towards the functional and prognostic role of PLK isoenzymes in human malignancies. The central role of PLK isoenzymes in tumorigenesis has been emphasised lately by studies showing that PLK1 inhibition, either by antisense or siRNA, leads to dramatic antiproliferative effects on tumour cells in vitro (Spänkuch-Schmitt et al, 2002a, b;Elez et al, 2003;Liu and Erikson, 2003), pointing at a potential therapeutic use of inhibitory strategies targeting PLK isoenzymes. In-depth expression analysis of members of the PLK family in various cancers and correlation with other tumour characteristics may thus provide the translational basis for such approaches in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…5 (ii). 15 H&E staining was performed and, as shown in Figure. 5A (iii) MPNST cells show enlarged nuclei, when compared to vehicle treated control at the same magnification, indicating polyploidy in vivo. By immunohistochemistry, mitotic arrest was not apparent (no induction of phospho histone H3 (Ser10).…”
Section: Polyploidy or Apoptotic In Vivomentioning
confidence: 99%
“…[8][9][10][11] Induction of apoptosis occurs in most tumor cells but not in normal cells upon interfering with PLK1 function, [12][13][14] and tumor regressions in mouse xenograft models has also been observed. 15,16 Based on these and other related studies, PLK1 has become a key target in cancer therapy and small-molecule inhibitors of PLK1 have become attractive candidates for anticancer drug development. Among several inhibitors targeting PLKs, some are at different stages of clinical development.…”
Section: Introductionmentioning
confidence: 99%